Efficacy of Transcranial Direct Current Stimulation to Improve Insight in Patients With Schizophrenia: A Systematic Review and Meta-analysis of Randomized Controlled Trials. (12th July 2022) - Adam, Ondine; Blay, Martin; Brunoni, Andre R; Chang, Hsin-An; Gomes, July S; Javitt, Daniel C; Jung, Do-Un; Kantrowitz, Joshua T; Koops, Sanne; Lindenmayer, Jean-Pierre; Palm, Ulrich; Smith, Robert C; et al.
Abstract: Background and Hypothesis: Impaired insight into the illness and its consequences is associated with poor outcomes in schizophrenia. While transcranial direct current stimulation (tDCS) may represent a potentially effective treatment strategy to relieve various symptoms of schizophrenia, its impact on insight remains unclear. To investigate whether tDCS would modulate insight in patients with schizophrenia, we undertook a meta-analysis based on results from previous RCTs that investigated the clinical efficacy of tDCS. We hypothesize that repeated sessions of tDCS will be associated with insight improvement among patients. Study Design: PubMed and ScienceDirect databases were systematically searched to identify RCTs that delivered at least 10 tDCS sessions in patients with schizophrenia. The primary outcome was the change in insight score, assessed by the Positive and Negative Syndrome Scale (PANSS) item G12 following active tDCS sessions as opposed to sham stimulation. Effect sizes were calculated for all studies and pooled using a random-effects model. Meta-regression and subgroup analyses were conducted. Study Results: Thirteen studies (587 patients with schizophrenia) were included. A significant pooled effect size (g) of −0.46 (95% CI [−0.78; −0.14]) in favor of active tDCS was observed. Age and G12 score at baseline were identified as significant moderators, while change in total PANSS score was not significant. Conclusions: Ten sessions of active tDCS with either frontotemporoparietal or bifrontal montage may improve insight into the illness in patients with schizophrenia. The effect of this treatment could contribute to the beneficial outcomes observed in patients following stimulation.